A numerical study of beam-to-column joints subjected to impact. (1st August 2016) - Grimsmo, E.L.; Clausen, A.H.; Aalberg, A.; Langseth, M.
Highlights: The numerical model was validated against previously reported tests. A good agreement between simulations and tests was observed. Changing the end-plate thickness increased the energy dissipated by the joint. Increasing the axial forces in the beams affected the response minimally. Increasing the inertia of the beams altered the failure mode of the joint. Abstract: Limited documentation is concerned with the behaviour of steel joints subjected to severe impulsive loading originating from incidents such as explosions or impact. In this paper, finite element simulations are used to investigate the behaviour of beam-to-column joints with bolted end-plate connections subjected to impact loading. An elastic-thermoviscoplastic material model was employed in the simulations. Good agreement was obtained between the simulations and previously reported tests in terms of both global and local behaviour. In particular, the numerical model successfully reproduced the experienced failure mode of tensile bolt fracture combined with end-plate deformation. The validated model was employed in investigations of three cases, in which the main findings are as follows: (1) reducing the end-plate thickness significantly increased the energy dissipated by the joint; (2) axial forces in the beams only marginally affected the response; and (3) including the additional inertia introduced by the presence of floor slabs may change the failure mode to premature shear failure.